(untitled) (Lundiana: International Journal of Biodiversity, 2009)
The genus Amazoneura Machado, 2004, regarded by Lencioni (2005) as a junior synonym of Forcepsioneura Lencioni, 1999, is revalidated based on morphological and zoogeographic evidence.